A sustainable human settlement morphology in a tropical humid environment ecology the case of San Jose de Buenavista, Antique - Cardenal, Joeffrey M. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
This ekistics theory research is concerned on the gradual and incremental evolutionary stages in the bio-physical and geo- political growth of the growth of the rural-urban or "rurban" region based on its ecological, economic, and social factors. In order to maintain the carrying capacity of the natural environment in a city-country realm, these triad components of sustainable development will be the integrative generic framework as rationale basis of the SPACE Classification System in its respective geographic functions that can serve as the principal blueprint for a comprehensive geometric form through the ecological Comprehensive Land Use Plan (e-CLUP) of the "ekisystem" (ekistics system) of the human settlement. As an attempt to analyze the processes of the tropical humid environment ecology data primary from geographic base and geo-hazard maps, it is hereby proposed to synthesize the patterns of sustainable human settlement morphology design by the Cardinal Place Model (CPM) for harmony and coordination. Although there is emphasis on the current imperative for technical definitions and descriptions from the salient empirical causes of climatological anomalies' input in the ecosystem, yet there is still an urgent implicative for physical decisions in designations to the sentient experiential effects of Climate Change (CC) impact on the ekisystem. One of the possible outcome scenarios will be the future of the earth's resources rapidly scarce supply which can be depleted due to rabidly scary demand of the ever increasing human population and compounded more by the destroyed ecosystem due to CC hazards and disasters that pose risks to society. This can imply for an alarming imbalance in the future extraction, production, distribution, and consumption of the goods and services in the whole urban region that would affect its socio-economic gain and spatio-ecologic growth for CC resiliency. It is encouraged then that the management of development should be directed only on the prime nodal-axial segment in the web network of the CPM as an important physical approach for connectivity, consistency, and continuity, hence promoting a sustainable location of urbanization. An alternative proposal beyond the prevailing focus on CC mitigation rather than the emergent pre-empting locus in CC adaptation during the early decades of the 21st century can be an appropriate human settlement planning with considerations on the Philippine tropical geography and colonial history. For its applications, the coastal and capital town of San Jose de Buenavista, in the province of Antique will be a case study area due to its potential progress as a fast urbanizing Local Government Unit (LGU) in the Western Visayas region that can also have its possible problems toward a fine modernizing municipality and eventually a city if not earlier anticipated. By proper orientation of its Physical Development Framework Plan (PDFP), the ecological comprehensive land use planning principles and tropical urban design zoning polices of the case study area can guide the LGU towards a sustainable human settlement morphology for its viability and vitality that adheres to the geo-climatic criteria as an embodiment of the P.L.A.C.E. concept-method, which is the phenomenological approach to the human-nature symbiotic relationship. It is hoped ultimately that this enlightened philosophical and political advocacy will promote the New Millennium ecological movement in both the local as well as the global environments to purse an urbane and humane society for all its sectoral constituents.